A Vasopressin-Induced Change in Prostaglandin Receptor Subtype Expression Explains the Differential Effect of PGE2 on AQP2 Expression - Deen, Peter M. T.; Boone, Michelle; Schweer, Horst; Olesen, Emma T. B.; Carmone, Claudia; Wetzels, Jack F. M.; Fenton, Robert A.; Kortenoeven, Marleen L. A. (Frontiers in Physiology, 2022)
Arginine vasopressin (AVP) stimulates renal urine concentration by increasing principal cell expression of aquaporin-2 (AQP2) water channels. PGE2 and PGF2α increase principal cell water absorption without AVP, but PGE2 decreases it in the presence of AVP. The underlying mechanism of this paradoxical response was investigated here. Mouse cortical collecting duct (mpkCCDcl4) cells mimic principal cells as they endogenously express AQP2 in response to AVP. PGE2 increased AQP2 abundance without dDAVP, while in the presence of dDAVP, PGE2 and PGF2α reduced AQP2 abundance. dDAVP increased cellular PGD2 and PGE2 release and decreased PGF2α release. mpkCCD cells expressed mRNAs for the receptors of PGE2 (EP1/EP4), PGF2 (FP) and TxB2 (TP). Incubation with dDAVP increased the expression of EP1 and FP but decreased the expression of EP4. In the absence of dDAVP, incubation of mpkCCD cells with an EP4, but not EP1/3, agonist increased AQP2 abundance, and the PGE2-induced increase in AQP2 was blocked with an EP4 antagonist. Moreover, in the presence of dDAVP, an EP1/3, but not EP4, agonist decreased the AQP2 abundance and the addition of EP1 antagonists prevented the PGE2-mediated downregulation of AQP2. Our study shows that in mpkCCDcl4 cells, reduced EP4 receptor and increased EP1/FP receptor expression by dDAVP explains the differential effects of PGE2 and PGF2α on AQP2 abundance with or without dDAVP. As the V2R and EP4 receptor, but not the EP1 and FP receptor, can couple to Gs and stimulate the cAMP pathway, our data support a view that cells can desensitize themselves for receptors activating the same pathway and sensitize themselves for receptors of alternative pathways.